Opportunities and prospects in the ready-food industry of Bangladesh and market share of Square Food & Beverage Limited in the industry. - Tasnim, Nishat (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.